THE ABILITY OF THE 2022/2023 ACADEMIC YEARS STUDENTS OF ENGLISH STUDY PROGRAM, ISLAMIC UNIVERSITY OF INDRAGIRI IN IDENTIFIYING BETWEEN TRANSITIVE AND INTRANSITIVE VERBS IN A SENTENCE - Agus Mustajib; Dahrial (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research was intended to find out the student’s ability in identifiying transitive and intransitive verbs in a sentence. The method used in this research was the descriptive quantitative research. The population of this research was the students of Islamic University of Indragiri. The sample of this research were 21 students at the first semester of English Study Program, Islamic University of Indragiri in the academic 2022/2023 years. In collecting the data, this research used written test (essay) as the research instrument to use to find out the students’ ability in identifiying transitive and intransitive verbs in a sentence. The students were asked to undeline whether transitive and intransitive verbs in a sentence. The total mean score was taken from two indicators, that were transitive verb with mean score 65.8 in a good level and intransitive verb with mean score 55.93 in an enough level. Based on the result of data, for both of indicators, their ability in identifiying transitive and intransitive verbs in a sentence were 59.58 in an enough level. In conclution, from the total mean score 50% the students can identify transitive and intransitive verbs in a sentence, but their ability in identifiying an intransitive verb was still limited.